2021
DOI: 10.3389/fcell.2021.636595
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of STAT1 in Ovarian Cancer: Insight Into Molecular Mechanisms and Application Potentials

Abstract: The signal transducer and activator of transcription 1 (STAT1) is a transducer protein and acts as a transcription factor but its role in ovarian cancer (OC) is not completely understood. Practically, there are two-faced effects of STAT1 on tumorigenesis in different kinds of cancers. Existing evidence reveals that STAT1 has both tumor-suppressing and tumor-promoting functions involved in angiogenesis, cell proliferation, migration, invasion, apoptosis, drug resistance, stemness, and immune responses mainly th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 133 publications
(159 reference statements)
1
18
0
Order By: Relevance
“…The interaction between miR-512-5p and STAT1 3′-UTR was proved by dual-luciferase reporter assay, which clarified that STAT1 was a direct target gene of miR-512-5p. Previous studies indicated that STAT1 was a double-edged sword in tumor progression [ 29 ]. Here the biological functions of STAT1 were explored and verified that STAT1 was an oncogene in BC.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between miR-512-5p and STAT1 3′-UTR was proved by dual-luciferase reporter assay, which clarified that STAT1 was a direct target gene of miR-512-5p. Previous studies indicated that STAT1 was a double-edged sword in tumor progression [ 29 ]. Here the biological functions of STAT1 were explored and verified that STAT1 was an oncogene in BC.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the standard treatment for OC is still cytoreductive surgery combined with platinum-based chemotherapy. However, resistance to cisplatin is the major obstacle of OC treatment, which is closely related to a poor prognosis ( Li X. et al, 2021 ). Therefore, a more accurate prediction of the effect of chemotherapy could reduce the financial and psychological burden of patients, and improve the overall prognosis to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…STAT1 plays a signi cant role in the progression and prognosis of various tumors such as gastric cancer, colorectal cancer, ovarian cancer and other tumors [18][19][20]. We all know that the combined of PD-1 and PD-L1 has a negative regulatory effect on the immune system in cancer patients.…”
Section: Discussionmentioning
confidence: 99%